Africa - Haugen, David M., 1969-; Musser, Susan (Detroit, MI : Greenhaven Press, 2012)
Presents a spectrum of viewpoints on topics significant to modern Africa, covering economics, foreign aid, AIDS, and relations with the United States.
How is Africa faring in the twenty-first century?: Africa's fortunes are improving / Charles Kenny -- Africa's fortunes are declining / Bruce Gilley -- Africa needs to expand free trade / Marian L. Tupy -- Free trade is devastating African economies / Gregory Elich -- Health care in Africa has not improved / Thompson Ayodele -- Africa is making strides in sustainable entrepreneurship / Helene Gallis -- Does Africa need foreign aid?: Foreign aid benefits Africa / Scott Baldauf -- Foreign aid does not benefit Africa / Mathew K. Jallow -- Africa needs trade, not only foreign aid / Richard Ilorah -- Africa needs good governance, not only foreign aid / Franklin Cudjoe -- Africa will progress without patronizing interference from the West / Andrew M. Mwenda -- What is the state of the AIDS epidemic in Africa?: AIDS is a serious threat in Africa / AVERT -- The threat of AIDS in Africa has been overstated / Michael Fumento -- Social and economic factors contribute to the spread of AIDS in Africa / Ben Wodi -- Political ignorance contributes to the spread of AIDS in Africa / Marco Evers -- AIDS is devastating Africa's children / Lawrence O. Gostin -- Treatment for African children with AIDS is expanding / Mark W. Kline -- What US policies will best serve Africa?: The United States should promote democracy in Africa / Russ Feingold -- The United States should stop promoting democracy in Africa / Roger Kaplan -- AFRICOM will help ensure African security / Robert Moeller -- AFRICOM will likely serve only US interests in Africa / Ed Blanche.
Includes bibliographical references (p. 232-236) and index.
Keywords: Investments, Foreign -- Africa; Economic development -- Africa; AIDS (Disease) -- Africa; Africa -- Economic conditions -- 21st century; Africa -- Foreign economic relations; United States -- Foreign relations -- Africa; Africa -- Foreign relations -- United States